Meeting the needs of our students: Developing engaged and employable citizens [PowerPoint] - Reddock, Rhoda (My University, 2015)
This presentation explores the following: 1) the role of education in our developing and global contexts, 2) the rise of credentialism in higher education, 3) student development as an investment in the future of the Caribbean and financial stability of the institution, 4) the role of student services in student development, and 5) challenges.
Contribution to the Panel on Meeting the Needs of Our Students: Developing Citizenship and Employability for the Twenty-First Century at the Regional Conference on Institutionalising Best Practice in Higher Education, UWI, St. Augustine, Trinidad and Tobago, 24-26 June, 2015.
Keywords: University students; Higher education; Student needs; Student services; Student university relationship; Student characteristics